The effect of COVID-19 on oncology pharmacy services: Results of a 3 month long weekly global survey. Issue 1 (12th January 2021) - Crul, Mirjam; Bosnak, Ahmet; Astier, Alain; Meier, Klaus
Abstract: Introduction: The COVID-19 pandemic has been felt in all areas of health care. We performed a weekly survey amongst the members of the European Society of Oncology Pharmacy (ESOP) to better understand its effects and how they evolved over time. We specifically studied alterations in the care for patients with cancer as well as in the work of oncology pharmacists. Methods: An online survey was developed by ESOP to compile data about the effects of COVID-19 on the work practices of professionals working in the field of oncology pharmacy. The survey was distributed electronically on a weekly basis from April 6 th to June 28 th . Results: A total of 1146 responses were gathered from respondents in 60 different countries. At any given time point, between 25% and 38% of the respondents had staff infected with COVID-19. In total, 29% of hospital pharmacists reported shortages of drugs necessary for the treatment of COVID-19 patients, and almost 50% also faced shortages of drugs necessary for the treatment of cancer patients. In addition, the majority of hospital pharmacists reported a decrease in planned surgery for oncology patients, as well as a decrease in the amount of chemotherapy preparations. Community pharmacists faced shortages of personal protective equipment in 40% of cases and shortages of drugs in 60%. Conclusion: The work of oncology pharmacists both in the clinical setting as well as in the community has been effected profoundly by the COVID-19 pandemic.